2020
DOI: 10.1186/s12992-020-00553-8
|View full text |Cite
|
Sign up to set email alerts
|

Health systems influence on the pathways of care for lung cancer in low- and middle-income countries: a scoping review

Abstract: Background: Globally, lung cancer is the most common cancer and cause of cancer-related deaths, responsible for nearly one in five deaths. Many health systems in low-and middle-income countries, including sub-Saharan Africa have weak organizational structure, which results in delayed lead time for lung cancer patient care continuum from diagnosis to palliative care. Aim: To map evidence on the health systems issues impacting on the delays in timely lung cancer care continuum from diagnosis to palliative care i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…15.2 ± 24.4 (median 10) days in this study. This is shorter than time periods reported from symptom onset to contact with a medical doctor in other countries, including 71 days in Nepal [44], 94 days in India [45], and 35 days or 49.9 ± 96.9 days in Turkey [16,46], however, these studies did not include informal providers as first contact. In this study, informal healthcare providers were the first choice for seeking healthcare reported by most respondents (60%), hence this duration is shorter than other studies mentioned above.…”
Section: Plos Onementioning
confidence: 84%
“…15.2 ± 24.4 (median 10) days in this study. This is shorter than time periods reported from symptom onset to contact with a medical doctor in other countries, including 71 days in Nepal [44], 94 days in India [45], and 35 days or 49.9 ± 96.9 days in Turkey [16,46], however, these studies did not include informal providers as first contact. In this study, informal healthcare providers were the first choice for seeking healthcare reported by most respondents (60%), hence this duration is shorter than other studies mentioned above.…”
Section: Plos Onementioning
confidence: 84%
“…It should be pointed out from the outset that the decision taken by the NIO to carry out specialized consultations on the same day for new patients contributes directly to reducing the overall waiting time, and the time to obtain an appointment with a specialist surgeon is cited as a signi cant phase in the patient pathway [11,[23][24][25]. The study has shown that the action of improving the quality of care at the hospital level could be handled in two ways: bottom-up creative strategies at the hospital level, and a topdown normative strategy from a more centralized level [26].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of health care systems in developed countries are little prepared to deal with this challenge, and many cancer patients globally will not have the privilege of early treatment. In these countries, nearly two-thirds of cancer patients die [ 6 ]. There is evidence that shows that in countries where national health services are well-developed, strategies such as early detection, treatment and survivorship care are improving the survival rates of many types of cancers [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%